2016
DOI: 10.5152/balkanmedj.2016.150317
|View full text |Cite
|
Sign up to set email alerts
|

Melanocytic Nevus of the Tarsal Conjunctiva

Abstract: Background: Melanocytic nevus is a rare occurrence in the tarsal conjunctiva and only 7 well-described cases have been reported previously in the English literature. Case Report: The medical records of 4 patients with tarsal conjunctival melanocytic nevus were reviewed, together with the relevant literature. All patients (3 women and 1 man; age range: 17 -40 years) had been referred with a suspicion of melanoma. There was one tarsal nevus in the lower eyelid in 3 patients and 2 nevi in the upper eyelid in 1 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A recent study reported 3 cases of blue nevi arising in the fornix [ 9 ]. Another case series reported 2 cases of melanocytic nevi involving the superior and inferior palpebral forniceal conjunctiva [ 10 ]. Previous cases reported in the literature of conjunctival forniceal nevi have had dark brown pigmentation (3 cases), intralesional cysts (2 cases), partial pigmentation (1 case), and moderate pigmentation (3 cases) [ 8 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported 3 cases of blue nevi arising in the fornix [ 9 ]. Another case series reported 2 cases of melanocytic nevi involving the superior and inferior palpebral forniceal conjunctiva [ 10 ]. Previous cases reported in the literature of conjunctival forniceal nevi have had dark brown pigmentation (3 cases), intralesional cysts (2 cases), partial pigmentation (1 case), and moderate pigmentation (3 cases) [ 8 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another case series reported 2 cases of melanocytic nevi involving the superior and inferior palpebral forniceal conjunctiva [ 10 ]. Previous cases reported in the literature of conjunctival forniceal nevi have had dark brown pigmentation (3 cases), intralesional cysts (2 cases), partial pigmentation (1 case), and moderate pigmentation (3 cases) [ 8 10 ]. Interestingly, the majority of prior cases reported in the literature were inferomedial in location, with only one previous report of a nevus involving the superior fornix.…”
Section: Discussionmentioning
confidence: 99%
“…altered pigmentation, size and vascularisation) may indicate the onset of a malignant transformation. Malignancy may also manifest as late onset conjunctival pigmented lesions, lesions located in the tarsal conjunctiva and conjunctival fornix as well as the absence of cysts on the surface of the lesion (1,2,5,12). Monitoring a group of 410 patients with conjunctival pigmented lesions, Shield et al noticed an increase of lesion size in 7% of cases, its altered colour in 5% of cases, darkening of conjunctival lesions in 13% cases and lesion growth in 8% of cases (2).…”
Section: Discussionmentioning
confidence: 99%